Dominance, Diversity and Regeneration Status of a Moist Sub-tropical Shorea robusta Gaertn. f. (Sal) Forest of Doon Valley, India - Chauhan, P. S.; Manhas, R. K.; Negi, J. D. S.; Singh, Lokender (Indian Forester, 2010)
Dominance, diversity and regeneration status of a moist sub-tropical sal forest in Doon valley was investigated. The results of the study reveal that S. robusta, Ardesia solanacea and Oplismenus compositus were the most dominant species in tree, shrub and herb layers respectively. Shrub layer was the most diverse strata, closely followed by the herb strata. Forest of Asarori are becoming more diverse and heterogeneous. Regeneration studies exhibited reverse ’J’ shaped curve for sal, which signifies good regeneration. But low conversion rate of seedlings to saplings requires proper management.